Cardiovascular Disease Risk Factors Awareness among Women with a History of Preeclampsia in Jordan - Manal Kassab RN, PhD; Evan Fadel Sabrah RN, MsC; Ahmad Smadi RN, PhD; Ahmad Rayan RN, CNS, PhD; Manal Hassan Baqeas RN, PhD student; Mohammad R. AlOsta RN, CNS, PhD; Elham H. Othman RN, CNS, PhD; Shereen Hamadneh RN, PhD (SAGE Publishing, 2023)
Introduction Preeclampsia is a pregnancy-specific hypertensive disease that affects 3-5% of pregnant women all over the world and 1.3% of pregnancies among Jordanian women. Objectives This study aims to assess the cardiovascular disease risk factors awareness among women with a recent history of preeclampsia in Jordan and assess the role of healthcare providers in providing counseling about cardiovascular disease risk factors. Methods A descriptive cross-sectional design was used to recruit 180 women with a recent history of preeclampsia during the last 12 months. Data were obtained from patients' medical records and the Attitude and Beliefs about Cardiovascular Disease Risk Questionnaires. Results The results revealed that 43.9% of women with a recent history of preeclampsia have hypertension, 6.7% have diabetes mellitus, 16.1% have dyslipidemia, 28.9% have a family history of cardiovascular disease, 66.1% are overweight or obese, and 7.2% are smokers. The mean total score of knowledge subscale was 5.5 (SD  =  1.21) out of 8. Only 20% of the participants had good cardiovascular disease knowledge. The mean total score of risk perception was 15.47 (SD  =  7.8). The mean score of perceived benefits and intention to change behaviors was 2.30 (SD  =  0.62). The mean score of healthy eating intentions was 2.54 (SD  =  0.81). Income, having diabetes mellitus, and receiving counseling about preeclampsia as cardiovascular disease risk factor were associated with some dimensions of cardiovascular disease risk factors awareness. Conclusion The prevalence of cardiovascular disease risk factors was relatively high among the study participants. The majority of participants had inadequate cardiovascular disease knowledge. In addition, the role of healthcare providers in providing counseling about cardiovascular disease and related risk factors, including PE was limited. Providing more counseling related to cardiovascular disease by nurses and doctors is essential to enhance women's cardiovascular disease knowledge and intention to change lifestyle.